Benefits and Barriers of Physical Activities among Technical University Students - Mohd Firdaus Abdullah; Mohamad Nizam Nazarudin; Rosli Saadan; Wan Ahmad Munsif Wan Pa; Mohd Radzani Abdul Razak (Akademia Baru, 2018)
This study aims to examine the perceptions of benefits and barriers to physical activity, especially workouts among Malaysian University Technical Network students (MTUN). In order to be educated and trained to become a highly skilled human resource that is able to contribute towards the vision of a world-class industrial nation, these students must be ensured to be physically fit and smart. Objectives: To examined perceived benefits and barriers of physical activities among Technical University students. Method: A total of 355 college students from each faculty in Universiti Teknikal Malaysia Melaka (UTeM) completed the Exercise Benefits/Barriers Scale. Findings: The greatest perceived benefit from exercise was physical performance followed by the benefits of psychological outlook, preventive health, life enhancement, and then social interaction. Physical performance was rated significantly higher than all other benefits. Psychological outlook and preventive health were not rated significantly different, although both were significantly higher than life enhancement and social interaction. Life enhancement was also rated significantly higher than social interaction. The greatest perceived barrier to exercise was physical exertion, which was rated significantly higher than time expenditure, exercise milieu, and family discouragement barriers. Implications from this investigation for the design of physical activity programmes include the importance, for females, of a perception of high benefit/barrier ratio that could be conducive to participation in exercise. Applied interventions need to assist students to ‘disengage’ from or overcome any perceived ‘unpleasantness’ of physical exertion during physical activity (decrease their perceived barriers), and to further highlight the multiple health and other benefits of regular exercising (increase their perceived benefits).